The Insertion of the Environmental Dimension in the Investment law - Hamoud, Sabrina (Journal of Legal Studies and Researches, 2023)
Protecting the environment means preserving it without damage or change that reduces its value. This requires taking certain measures and measures to achieve this protection, which is called the environmental policy. This study aims to clarify the relationship between the environment and development in an attempt to reach the concept of sustainable development.